(untitled) (Journal of Health Sciences, 2018)
Introduction: Lumbar Disk Herniation with Radiculopathy (LDHR) appears to be a large and costly problem. The paradigm regarding the best treatment for LDHR has being between surgery and conservative management. The aim of this study was to compare and summarize evidence regarding the effectiveness of surgery and conservative treatment for individuals with sciatica due to lumbar disc herniation. Methods: This study reviewed all literatures published on individuals with LDHR, who were managed either via surgery or conservative method. Pain and functional disability were the main outcome measures analyzed. A comprehensive search of PubMed, TRIP, PEDro and CINAHL was conducted from October, 2011 to June 2017. Two independent researchers selected the studies, and extracted the data. Methodological quality was assessed using the PEDro scale. Meta-analysis was carried out where suitable. Results: Eight studies involving (n=1,507) were included in the review. Meta-analysis was conducted for only 4 studies (n=784). The meta-analysis showed significant benefit for early surgery than conservative care -8.01(95% CI, -9.27 to -6.72) in the short-term effect -0.49 (95% CI, -0.7 to -0.28). However, the result for long-term effect did not show any significant difference between surgery and conservative care 1.60 (95% CI, -6.85 to 10.05). Conclusion: This current evidence suggest that early surgery for individuals with lumbar disc herniation with radiculopathy is better than conservative care in the short-term without any long-term difference. The results of this review should be interpreted with caution as the populations of the included studies were largely heterogeneous.